Protease alcalina na alimentação de suínos na fase de crescimento e terminação - Arndt, Stefani Natani dos Santos (2022)
The dependence on ingredients such as soybean meal in swine feed influences directly the cost of production, intensifying studies involving the use of feed additives as the protease enzyme. The objective of this study was to evaluate the addition of alkaline protease in diets, with and without reduction of crude protein (PB), for growing-finishing pigs, on zootechnical performance, apparent digestibility of nutrients, blood parameters and carcass and meat attributes. A total of 40 male pigs with initial body weight of 26.28 ± 1.24 kg were allocated in a completely randomized experimental design, consisting of five treatments: (1) CP: positive control, without PB reduction and without enzyme, and (2) CP + 0.30: CP with the addition of 0.30 kg of enzyme/t of feed (3) CN: negative control, with a reduction of 2 and 1% of the PB content in the growth and finishing phases, respectively, without enzyme, (4) CN + 0.15: CN with addition of 0.15 kg of enzyme/t of feed, (5) CN + 0.30: CN with addition of 0.30 kg of enzyme/t of feed, with eight repetitions, with the animal as the experimental unit. The results indicated that there was a treatment effect on average daily feed intake (CRDM), daily body weight gain (GPCD) and feed efficiency (EA) for pigs in growth phase II (P<0.0001, P= 0.0398 and P=0.0007). Through the analysis of orthogonal contrasts, it was observed that the CN animals had (P≤0.05) greater EA compared to those that consumed CN+0.15 and CN+0.30, although the worst GPCD and lowest CRDM was verified for the animals that received CN+0.30. There was no effect (P>0.05) of treatment on the zootechnical performance variables in the finishing phase, although an inclination (P=0.0729) was observed on the GPCD. There was an effect (P≤0.05) on apparent digestibility coefficient of dry matter (CDAMS), digestible dry matter (MSD), apparent digestibility coefficient of organic matter (CDAMO), digestible organic matter (MOD) and available protein (PD) in growing phase II. Comparisons among the average of treatments tested by orthogonal contrasts indicated that animals from the CN treatment showed a reduction in CDA when compared to CN+0.15 and CN+0.30. In finishing phase II, there was a difference (P≤0.05) on MSD, CDAMO, MOD, PD and digestibility coefficient apparent of gross energy (CDAEB). The results indicated that CN animals had lower CDA when compared to those that received CN+0.15 and CN+0.30, except for PD. There was no effect (P>0.05) of treatments on blood parameters in growth phase II. However, in the finishing phase II, the pigs in the CP group showed (P≤0.05) an increase of 27.65% in albumin concentration compared to those with CP+0.30. Also, animals in the CP group had (P≤0.05) an increase in PT and globulin concentrations compared to those in the CN group. The pigs that consumed the treatment based on CN and CP+0.30 showed (P≤0.05) an increase in the luminosity of the longissimus thoracis muscle compared to the CP, as well as it was verified (P=0.015) greater luminosity in the piglet muscle from the CN group compared to the CP group. In conclusion, the reduction of PB in the diet by 2% and 1%, growth and finishing respectively, maintaining the amino acid supplementation up to valine, does not modify performance, blood characteristics, carcass and meat characteristics. The addition of the protease enzyme improves digestibility.